Digital farmer registry and tailored extension and advisory services in Ethiopia: A process evaluation - Sebsibie, Samuel; Ketema, Dessalegn Molla; Abate, Gashaw T. (International Food Policy Research Institute, 2023)
Ethiopia hosts one of the largest extension systems in Africa, with approximately 43 development agents (DAs) per 10,000 farmers, more than 15,000 farmers training centers (FTCs) that serve as a focal point for agricultural development activities at the local level, and 25 Agricultural Technical Voca tional Education and Training (ATVET) institutes that prepare and update extension staff in both general and specialized fields of expertise (Berhane et al. 2018; ATA 2014; Davis et al. 2010). DAs report edly reach more than 75% of farm households in the country (CSA 2017), and every kebele hosts an average of three DAs, each with his or her own specialization. However, there are concerns about the quality of extension and advisory services DAs provide mainly because DAs are overburdened and under-resourced. DAs actively engage in activities that do not typically fall under the mandate of agricultural extension services, including the collection of taxes, loan repayments and mobilization of labor for public works. A related concern is the simple “technology-push” approach to agricultural intensification followed by most DAs since they do not have the time to closely know the farmers and provide a more “tailored and knowledge-driven” advisory that puts farmers’ priorities and technical capabilities at the center of DA’s effort (Berhane et al. 2018; Bachewe et al. 2017).